Spinning oil and application thereof

By using specific proportional spinning oil agents in the spinning process of implantable medical fibers, the fiber electrostatic and biocompatibility problems are solved, the cleaning process is reduced, the production cost is reduced, and the fiber spinning is improved. and biocompatibility.

CN119433987APending Publication Date: 2025-02-14HANGZHOU REJOIN MASTIN MEDICAL INSTR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411784066.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

During the spinning process of implantable medical fibers, existing spinning oil agents have electrostatic problems and are difficult to ensure biocompatibility and safety, resulting in the finished fibers undergoing complex cleaning processes and increasing production costs.

Method used

A spinning oil agent is used, containing 74.5% to 93.9% by weight of purified water, 5% to 20% by weight of polyethylene glycol, 1% to 5% by weight of polyvinyl alcohol, and 0.1% to 0.5% by weight of poly Vinylpyrrolidone has a conductivity of 4.0×10-4S/cm~6.0×10-4S/cm, and has good antistatic properties, bundling properties, emulsification and biocompatibility.

Benefits of technology

The spinning oil agent not only improves the spinningability and biocompatibility of the fibers, reduces the cleaning process, and reduces production costs. At the same time, due to its excellent stability, no need for low-temperature storage or additional preservatives are added, and the frequency of replacement during use is changed during use Lower, with significant cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005173888610000121
    Figure BDA0005173888610000121
  • Figure BDA0005173888610000131
    Figure BDA0005173888610000131
  • Figure BDA0005173888610000141
    Figure BDA0005173888610000141
Patent Text Reader

Abstract

The invention relates to the technical field of medical fiber spinning auxiliaries, in particular to spinning oil and application thereof.The spinning oil is prepared from 74.5 wt%-93.9 wt% of purified water, 5 wt%-20 wt% of polyethylene glycol, 1 wt%-5 wt% of polyvinyl alcohol and 0.1 wt%-0.5 wt% of polyvinylpyrrolidone, and the conductivity of the spinning oil is 4.0 * 10 <-4 > S / cm to 6.0 * 10 <-4 > S / cm; the spinning oil provided by the invention has both fiber spinnability and good biocompatibility, is high in safety when being used as an implant-grade medical material, and is especially suitable for preparing implant-grade medical fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of spinning aids, and in particular to a spinning oil and application thereof. Background Art

[0002] Implant-grade medical fibers are mainly fibers for Class III medical device products used in the human body. The textiles made from them mainly include surgical sutures, stents, hollow fiber tubes, medical dressings, periodontal regeneration sheets, reinforced mesh fabrics, and medical fiber paper to prevent adhesion of internal organs after surgery. Implant-grade medical fibers can be divided into non-absorbable fibers and absorbable fibers according to their degradation or human absorbability. Non-absorbable fibers include ultra-high molecular weight polyethylene (UHMWPE) fibers, polyethylene terephthalate (PET) fibers, polyamide 6 (PA6) or polyamide 66 (PA66) fibers, and polypropylene (PP) fibers, while absorbable fibers include polydioxanone (PDS) fibers, polyvinyl alcohol (PVA) fibers, polyglycolic acid (PGA) fibers, and polylactide-glycolide (PGLA) fibers.

[0003] During the spinning process of implant-grade medical fibers, due to the high spinning speed, they will constantly rub against the spinning equipment and generate static electricity. The accumulation of static electricity will cause the fibers to repel each other and spread out, affecting the fiber molding and quality, and in severe cases, the fibers cannot be molded. In the production process of fibers, the application of oil is indispensable, mainly used to adjust the friction coefficient of the fibers, and provide the fibers with appropriate cohesion and antistatic properties during the spinning process. The appropriate cohesion of the fibers can ensure that semi-finished products such as fiber rolls, fiber strips, rovings and yarns have a certain strength, which is a necessary condition for the fabric to maintain good dimensional stability; and if the electrostatic performance is not properly controlled, it will cause a series of problems such as fiber winding around the needle cloth, winding around the roller, and increasing the breakage rate, so that the processing process cannot proceed smoothly, seriously affecting the processing efficiency. Therefore, the oil plays a vital role in the stability of spinning production and product quality.

[0004] For implantable medical fibers, the spinning oil used must have both fiber spinnability and safety. However, since the spinning oils on the market are mainly used in the field of conventional chemical fibers, they only consider fiber spinnability without considering safety to the human body. For this reason, medical fiber manufacturers and users, especially implantable medical fiber manufacturers, often need to perform a series of complex cleaning processes on finished fiber products and corresponding textiles, such as using ultrasonic, circulating, high temperature, high pressure, high fluidity and other cleaning methods to reduce the amount of spinning oil residue and improve the cleaning effect of fibers and corresponding textiles to avoid safety risks in subsequent clinical use. However, these complex processes undoubtedly increase the production cost of the product.

[0005] In addition, conventional spinning oils contain many uncontrollable chemical components, such as surfactants, lubricants, emulsifiers and antistatic agents. These chemical components will become corrupt due to bacterial growth if left for a long time. Therefore, in order to reduce bacterial growth, conventional spinning oils usually need to be stored at low temperatures, and in order to ensure the effectiveness of use, they are often used in combination with preservatives. Despite this, conventional spinning oils still cannot avoid carrying initial contamination bacteria, which will enter the surface and interior of the finished fiber during the spinning process, causing fiber contamination and posing a greater safety risk. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a spinning oil having good biocompatibility and fiber spinnability, which is particularly suitable for preparing implant-grade medical fibers.

[0007] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a spinning oil, comprising 74.5wt% to 93.9wt% of purified water, 5wt% to 20wt% of polyethylene glycol, 1wt% to 5wt% of polyvinyl alcohol and 0.1wt% to 0.5wt% of polyvinyl pyrrolidone, and the conductivity of the spinning oil is 4.0×10 -4 S / cm~6.0×10 -4 S / cm.

[0008] In one embodiment, the viscosity of the spinning oil is 20 mm 2 / s~50mm 2 / s.

[0009] In one embodiment, the conductivity of the polyethylene glycol is 1.5×10 -4 S / cm~6.5×10 -4 S / cm.

[0010] In one embodiment, the polyethylene glycol is selected from at least one of polyethylene glycol 200, polyethylene glycol 300, polyethylene glycol 400, polyethylene glycol 500 or polyethylene glycol 600.

[0011] In one embodiment, the weight average molecular weight of the polyvinyl alcohol is 8000 to 50000;

[0012] And / or, the alcoholysis degree of the polyvinyl alcohol is greater than or equal to 80%.

[0013] In one embodiment, the weight average molecular weight of the polyvinyl pyrrolidone is 8000 to 50000;

[0014] And / or, the K value of the polyvinyl pyrrolidone is 13-30.

[0015] In one embodiment, the mass ratio of the polyethylene glycol to the polyvinyl alcohol is (1-5):1.

[0016] The present invention also provides the use of the spinning oil as described above in the spinning of implant-grade medical fibers.

[0017] In one embodiment, the oiling rate of the spinning oil agent is 0.2% to 1.5%.

[0018] In one embodiment, the implant-grade medical fiber is one of UHMWPE fiber, PET fiber, PA fiber, PDS fiber, and PLGA fiber.

[0019] The invention provides the spinning oil with a specific content of purified water, polyethylene glycol, polyvinyl alcohol and polyvinyl pyrrolidone through synergistic effect. -4 S / cm~6.0×10 -4 The conductivity of S / cm. The spinning oil of the present invention has good antistatic properties, clustering, emulsification and biocompatibility, broadens the application of spinning oil in implant-grade medical fiber spinning, and is applicable to a wide range of implant-grade medical spinning fiber types. The medical fiber spun by the spinning oil of the present invention only needs simple surface cleaning or even no cleaning process after being made into implant-grade medical textiles to meet the biocompatibility requirements of implant-grade medical materials. Compared with conventional spinning oils for chemical fibers, the spinning oil of the present invention has excellent stability, does not need to be stored at low temperatures, and does not need to add additional preservatives before use to inhibit bacterial growth, and the components of the spinning oil have good mutual solubility, basically no stratification, and the frequency of replacement of the spinning oil during use is lower; at the same time, the spinning oil of the present invention has low viscosity and better oiling uniformity, which can ensure the spinnability of the fiber at a lower dosage, thereby reducing the waste of the oil, and has a significant cost advantage; furthermore, the spinning oil of the present invention is not easy to volatilize, has no irritating odor, and is more friendly to workshop operators when used. DETAILED DESCRIPTION

[0020] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.

[0022] The present invention provides a spinning oil as an implantable medical fiber material, comprising 74.5wt% to 93.9wt% of purified water, 5wt% to 20wt% of polyethylene glycol, 1wt% to 5wt% of polyvinyl alcohol and 0.1wt% to 0.5wt% of polyvinyl pyrrolidone, and the electrical conductivity of the spinning oil is 4.0×10 -4 S / cm~6.0×10 -4 S / cm.

[0023] The spinning oil provided by the present invention has good antistatic properties, clustering, emulsification and biocompatibility, broadens the application of spinning oil in implant-grade medical fiber spinning, and is applicable to a wide range of implant-grade medical spinning fiber types. The medical fiber spun by the spinning oil only needs simple surface cleaning or even no cleaning process after being made into implant-grade medical textiles to meet the biocompatibility requirements of implant-grade medical materials. Compared with conventional spinning oils for chemical fibers, the spinning oil of the present invention has excellent stability, does not need to be stored at low temperatures, and does not need to add additional preservatives before use to inhibit bacterial growth. The components of the spinning oil have good mutual solubility, are basically not stratified, and the frequency of replacement of the spinning oil during use is lower; at the same time, the spinning oil of the present invention has low viscosity and better oiling uniformity, can ensure fiber spinnability at a lower dosage, thereby reducing oil waste, and has significant cost advantages; furthermore, the spinning oil of the present invention is not easy to volatilize, has no irritating odor, and is more friendly to workshop operators when used.

[0024] Specifically, in the spinning oil, the mass fraction of purified water includes but is not limited to any point value among 74.5wt%, 74.6wt%, 75wt%, 80wt%, 85wt%, 87.9wt%, 90wt%, 93.9wt% or a range value between any two of them; the mass fraction of polyethylene glycol includes but is not limited to any point value among 5wt%, 6wt%, 10wt%, 12wt%, 15wt%, 18wt%, 20wt% or a range value between any two of them; the mass fraction of polyvinyl alcohol includes but is not limited to any point value among 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or a range value between any two of them; the mass fraction of polyvinyl pyrrolidone includes but is not limited to any point value among 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt% or a range value between any two of them.

[0025] In one embodiment, the viscosity of the spinning oil is preferably 20 mm 2 / s~50mm 2 / s, when using spinning oil to prepare implant-grade medical fibers, it is more conducive to ensuring the uniformity of oiling, while controlling the amount of spinning oil used while ensuring spinnability, thereby further reducing the cost of use.

[0026] Specifically, the viscosity of the spinning oil includes but is not limited to 20 mm 2 / s, 25mm 2 / s, 30mm 2 / s, 35mm 2 / s, 40mm 2 / s, 45mm 2 / s, 50mm 2 / s, or any range of values ​​between them.

[0027] It can be understood that the purified water used in the present invention refers to water with almost no impurities except water molecules. Preferably, the purified water meets the requirements of the "Pharmacopoeia of the People's Republic of China (Part II)": pharmaceutical water obtained by distillation, ion exchange, reverse osmosis or other suitable methods, without any additives.

[0028] The polyethylene glycol in the spinning oil has not only good water solubility, but also good antistatic property, bundling property and emulsifying effect, and can eliminate static electricity generated during fiber friction, making the fiber softer. As an auxiliary agent, it is widely used in the fields of cosmetics industry and pharmaceutical industry.

[0029] Preferably, the conductivity of the polyethylene glycol is 1.5×10 -4 S / cm~6.5×10 -4S / cm, including but not limited to 1.5×10 -4 S / cm, 2.0×10 -4 S / cm, 3.0×10 -4 S / cm, 4.0×10 -4 S / cm, 5.0×10 -4 S / cm, 6.0×10 - 4 S / cm, 6.5×10 -4 S / cm, or any range between them.

[0030] Preferably, the polyethylene glycol is selected from at least one of polyethylene glycol 200, polyethylene glycol 300, polyethylene glycol 400, polyethylene glycol 500 or polyethylene glycol 600.

[0031] It can be understood that the polyethylene glycol in the spinning oil can be a single component, for example: polyethylene glycol 200, polyethylene glycol 300, polyethylene glycol 400, polyethylene glycol 500 or polyethylene glycol 600, or it can be a mixed component of two or more, for example: a mixture of polyethylene glycol 200 and polyethylene glycol 300, a mixture of polyethylene glycol 400 and polyethylene glycol 500, a mixture of polyethylene glycol 200, polyethylene glycol 500 and polyethylene glycol 600, etc.

[0032] The polyvinyl alcohol in the spinning oil has an emulsifying effect, which is beneficial to reducing the surface tension of the fiber and making the fiber have better cohesion. At the same time, polyvinyl alcohol is a highly safe high-molecular organic substance, which is non-toxic to the human body, has no side effects, and has good biocompatibility.

[0033] Preferably, the weight average molecular weight (M w ) is 8000-50000, including but not limited to any value among 8000, 9000, 10000, 20000, 30000, 40000, 50000 or any range between two values.

[0034] More preferably, the weight average molecular weight (M w ) is 8000~20000.

[0035] Preferably, the alcoholysis degree of the polyvinyl alcohol is greater than or equal to 80%, including but not limited to any point value among 80%, 85%, 90%, 95% or any range value between two of them.

[0036] More preferably, the alcoholysis degree of the polyvinyl alcohol is greater than or equal to 95%.

[0037] It can be understood that the polyvinyl alcohol in the spinning oil can be a single component, for example: polyvinyl alcohol with a weight average molecular weight of 10,000 or polyvinyl alcohol with a weight average molecular weight of 20,000, polyvinyl alcohol with a degree of alcoholysis of 85% or polyvinyl alcohol with a degree of alcoholysis of 90%, or it can be a mixed component, for example: a mixture of polyvinyl alcohol with a weight average molecular weight of 10,000 and polyvinyl alcohol with a weight average molecular weight of 20,000, and a mixture of polyvinyl alcohol with a degree of alcoholysis of 85% and polyvinyl alcohol with a degree of alcoholysis of 90%.

[0038] The polyvinyl pyrrolidone in the spinning oil is used as a surfactant, which is beneficial to improving the bundling property of the fiber. Meanwhile, as one of the pharmaceutical excipients, the polyvinyl pyrrolidone also has good biocompatibility.

[0039] Preferably, the weight average molecular weight (M) of the polyvinyl pyrrolidone w ) is 8000-50000, including but not limited to any value among 8000, 10000, 15000, 20000, 30000, 40000, 50000 or any range between two values.

[0040] More preferably, the weight average molecular weight (M w ) is 8000~15000.

[0041] Preferably, the K value of the polyvinyl pyrrolidone is 13-30, including but not limited to any point value among 13, 14, 15, 16, 17, 18, 28, 30 or a range between any two of them.

[0042] More preferably, the K value of the polyvinyl pyrrolidone is 13-16.

[0043] It should be noted that the K value is usually used to characterize the average molecular weight of polyvinyl pyrrolidone. Different K values ​​represent the corresponding average molecular weight range of polyvinyl pyrrolidone. At the same time, the K value also represents the relative viscosity characteristic value of the polyvinyl pyrrolidone aqueous solution. Generally, the larger the K value, the greater the viscosity of the polyvinyl pyrrolidone and the stronger the adhesion.

[0044] Preferably, the mass ratio of the polyethylene glycol to the polyvinyl alcohol is (1-5):1, including but not limited to any point value of 1:1, 2:1, 3:1, 4:1, 5:1 or a range value between any two of them. Further preferably, the mass ratio of the polyethylene glycol to the polyvinyl alcohol is (2-5):1.

[0045] It should be noted that the present invention does not limit the preparation method of the spinning oil. Since the spinning oil uses a small amount of raw materials and the raw materials can be stored separately for a long time, it can be used immediately only by simple heating, dissolving and mixing according to the corresponding raw material ratio. For example: first add purified water to the stirring device, heat to 80°C~95°C, then add polyvinyl alcohol to dissolve, and after the dissolution is completed, add polyethylene glycol and polyvinyl pyrrolidone in sequence, and stir well to obtain the spinning oil.

[0046] The present invention also provides an application of the above-mentioned spinning oil in the spinning of implantable medical fibers. It is understandable that the present invention does not limit the specific application process of implantable medical fibers, and the spinning oil provided by the present invention can be prepared by referring to the existing conventional preparation method, which will not be described in detail in the present invention.

[0047] The spinning oil described in the present invention is used to prepare implantable medical fibers. On the basis of ensuring the spinnability of the fibers, the deficiency that fibers prepared with traditional spinning oils are difficult to be applied to implantable medical textiles is overcome. The prepared implantable medical fibers and textiles (such as sutures, stents, patches, etc.) prepared from the implantable medical fibers have good biocompatibility and only require simple surface cleaning or even no cleaning and can be directly sterilized, packaged and used, which not only improves the clinical use safety of implantable medical textiles, but also significantly reduces the cleaning cost. In addition, both non-absorbable fibers and absorbable fibers in implantable medical fibers are applicable.

[0048] In one embodiment, the oiling rate of the spinning oil is preferably 0.2% to 1.5%. It should be noted that the oiling rate refers to the mass fraction of the spinning oil attached to the fiber in the spinning process. When the oiling rate of the spinning oil is too high, it may lead to increased oil pollution; when the oiling rate of the spinning oil is too low, the fiber will become loose, the friction resistance will increase, and problems such as hair will occur.

[0049] In one embodiment, the implant-grade medical fibers include but are not limited to non-absorbable fibers and absorbable fibers. Specifically, the non-absorbable fibers include but are not limited to medical UHMWPE fibers, medical PET fibers or medical PA fibers, and the absorbable fibers include but are not limited to medical PDS fibers or medical PLGA fibers.

[0050] The spinning oil and its application will be further described below by the following specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are followed. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0051] Example 1

[0052] 87.9 wt% purified water was added to the stirred tank, heated to 90°C, and 2 wt% polyvinyl alcohol (weight average molecular weight M w =8000, alcoholysis degree of 98%) was dissolved, and then 10wt% of polyethylene glycol 200 (conductivity of 3.9×10 -4 S / cm) and 0.1wt% polyvinyl pyrrolidone (weight average molecular weight M w =10000, K13), stir evenly to obtain spinning oil.

[0053] The test showed that the conductivity of the spinning oil prepared in this embodiment was 5.1×10 -4 S / cm, viscosity is 23mm 2 / s.

[0054] Example 2

[0055] 74.5 wt% purified water was added to the stirred tank and heated to 95°C. 5 wt% polyvinyl alcohol (weight average molecular weight M w =8000, alcoholysis degree of 99%) was dissolved, and then 20wt% of polyethylene glycol 300 (conductivity of 1.7×10 -4 S / cm) and 0.5wt% polyvinyl pyrrolidone (weight average molecular weight M w =8000, K14), stir evenly to obtain spinning oil.

[0056] The test shows that the conductivity of the spinning oil prepared in this embodiment is 5.9×10 -4 S / cm, viscosity is 49mm 2 / s.

[0057] Example 3

[0058] 93.9 wt% purified water was added to the stirred tank and heated to 95°C. 1 wt% polyvinyl alcohol (weight average molecular weight M w =20000, alcoholysis degree of 95%) was dissolved, and then 5wt% of polyethylene glycol 200 (conductivity of 6.3×10 -4 S / cm) and 0.1wt% polyvinyl pyrrolidone (weight average molecular weight M w =15000, K16), stir evenly to obtain spinning oil.

[0059] The test shows that the conductivity of the spinning oil prepared in this embodiment is 4.5×10 -4 S / cm, viscosity is 21mm 2 / s.

[0060] Example 4

[0061] 74.6 wt% purified water was added to the stirred tank and heated to 95°C. 5 wt% polyvinyl alcohol (weight average molecular weight M w =15000, alcoholysis degree of 99%) was dissolved, and then 20wt% of polyethylene glycol 300 (conductivity of 6.3×10 -4 S / cm) and 0.4wt% polyvinylpyrrolidone (weight average molecular weight M w =10000, K15), stir evenly to obtain spinning oil.

[0062] The test showed that the conductivity of the spinning oil prepared in this embodiment was 5.8×10 -4 S / cm, viscosity 50mm 2 / s.

[0063] Example 5

[0064] 87.9 wt % of purified water was added to the stirred tank, heated to 90°C, and 5 wt % of polyvinyl alcohol (weight average molecular weight M w =8000, alcoholysis degree of 98%) was dissolved, and then 7wt% of polyethylene glycol 200 (conductivity of 3.9×10 -4 S / cm) and 0.1wt% polyvinyl pyrrolidone (weight average molecular weight M w =10000, K13), stir evenly to obtain spinning oil.

[0065] The test shows that the conductivity of the spinning oil prepared in this embodiment is 4.1×10 -4 S / cm, viscosity is 32mm 2 / s.

[0066] Example 6

[0067] 87.9 wt% of purified water was added to the stirred tank, heated to 90°C, and 3 wt% of polyvinyl alcohol (weight average molecular weight M w =8000, alcoholysis degree of 98%) was dissolved, and then 9wt% of polyethylene glycol 200 (conductivity of 3.9×10 -4 S / cm) and 0.1wt% polyvinyl pyrrolidone (weight average molecular weight M w =10000, K13), stir evenly to obtain spinning oil.

[0068] The test showed that the conductivity of the spinning oil prepared in this embodiment was 5.0×10 -4 S / cm, viscosity 25mm 2 / s.

[0069] Comparative Example 1

[0070] 94.6 wt% purified water was added to the stirred tank and heated to 95°C. 5 wt% polyvinyl alcohol (weight average molecular weight M w =15000, alcoholysis degree 99%) was dissolved, and after the dissolution was completed, 0.4wt% of polyvinyl pyrrolidone (weight average molecular weight M w =10000, K15), stir evenly to obtain spinning oil.

[0071] After testing, the conductivity of the spinning oil prepared in this comparative example is 3.2×10 -4 S / cm, viscosity 18mm 2 / s.

[0072] Comparative Example 2

[0073] 89.9 wt% purified water was added to the stirred tank, and 10 wt% polyethylene glycol 200 (conductivity of 3.9×10 -4 S / cm) and 0.1wt% polyvinyl pyrrolidone (weight average molecular weight M w =10000, K13), stir evenly to obtain spinning oil.

[0074] After testing, the conductivity of the spinning oil prepared in this comparative example is 3.9×10 -4 S / cm, viscosity is 36mm 2 / s.

[0075] Comparative Example 3

[0076] 88.0 wt% purified water was added to the stirred tank, heated to 90°C, and 2 wt% polyvinyl alcohol (weight average molecular weight M w =8000, alcoholysis degree 98%) was dissolved, and then 10wt% of polyethylene glycol 200 (conductivity 3.9×10 -4 S / cm), stir evenly to obtain spinning oil.

[0077] After testing, the conductivity of the spinning oil prepared in this comparative example is 4.1×10 -4 S / cm, viscosity is 21mm 2 / s.

[0078] Comparative Example 4

[0079] 84 wt% purified water was added to the stirred tank, heated to 90°C, and 5 wt% polyvinyl alcohol (weight average molecular weight M w=8000, alcoholysis degree of 98%) was dissolved, and then 10wt% of polyethylene glycol 200 (conductivity of 3.9×10 -4 S / cm) and 1wt% polyvinyl pyrrolidone (weight average molecular weight M w =10000, K13), stir evenly to obtain spinning oil.

[0080] After testing, the conductivity of the spinning oil prepared in this comparative example is 4.3×10 -4 S / cm, viscosity is 56mm 2 / s.

[0081] Comparative Example 5

[0082] 79.5 wt% purified water was added to the stirred tank and heated to 90°C. 10 wt% polyvinyl alcohol (weight average molecular weight M w =8000, alcoholysis degree of 98%) was dissolved, and then 10wt% of polyethylene glycol 200 (conductivity of 3.9×10 -4 S / cm) and 0.5wt% polyvinyl pyrrolidone (weight average molecular weight M w =10000, K13), stir evenly to obtain spinning oil.

[0083] After testing, the conductivity of the spinning oil prepared in this comparative example is 5.9×10 -4 S / cm, viscosity is 54mm 2 / s.

[0084] Comparative Example 6

[0085] 89 wt% purified water was added to the stirred tank, heated to 90°C, and 0.5 wt% polyvinyl alcohol (weight average molecular weight M w =8000, alcoholysis degree of 98%) was dissolved, and then 10wt% of polyethylene glycol 200 (conductivity of 3.9×10 -4 S / cm) and 0.5wt% polyvinyl pyrrolidone (weight average molecular weight M w =10000, K13), stir evenly to obtain spinning oil.

[0086] After testing, the conductivity of the spinning oil prepared in this comparative example is 3.8×10 -4 S / cm, viscosity 40mm 2 / s.

[0087] Comparative Example 7

[0088] 74.5 wt% purified water was added to the stirred tank and heated to 90°C. 1 wt% polyvinyl alcohol (weight average molecular weight Mw =8000, alcoholysis degree of 98%) was dissolved, and then 24wt% of polyethylene glycol 200 (conductivity of 6.8×10 -4 S / cm) and 0.5wt% polyvinyl pyrrolidone (weight average molecular weight M w =10000, K13), stir evenly to obtain spinning oil.

[0089] After testing, the conductivity of the spinning oil prepared in this comparative example is 7.2×10 -4 S / cm, viscosity is 49mm 2 / s.

[0090] Comparative Example 8

[0091] 93.5 wt% purified water was added to the stirred tank and heated to 90°C. 2 wt% polyvinyl alcohol (weight average molecular weight M w =8000, alcoholysis degree of 98%) was dissolved, and then 4wt% of polyethylene glycol 200 (conductivity of 1.5×10 -4 S / cm) and 0.5wt% polyvinyl pyrrolidone (weight average molecular weight M w =10000, K13), stir evenly to obtain spinning oil.

[0092] After testing, the conductivity of the spinning oil prepared in this comparative example is 2.1×10 -4 S / cm, viscosity 25mm 2 / s.

[0093] The spinning oils prepared in all embodiments and comparative examples were tested in the spinning process of UHMWPE fiber, PET fiber, PA66 fiber, PDS fiber and PLGA fiber, respectively, to evaluate the oiling rate and spinnability, and the test results are shown in Table 1. Among them, the oiling rate was tested according to GB / T 6504-2017 standard; spinnability is a subjective evaluation standard for spinning conditions, hairy yarns, and finished product performance, such as: whether there is a break, the frequency of break, the hairy yarn situation after no break (more, less, etc.), the performance of the finished product with less hairy yarns and whether it meets the requirements, etc. to comprehensively judge the spinnability. According to the dimensions of the frequency of break, the amount of hairy yarns, whether the finished product is easy to break, etc., the spinnability is graded: good - no break, basically no hairy yarns, and the finished product is not easy to break; good - no break, less hairy yarns, and the finished product is not easy to break; medium - the frequency of break is high, and the hairy yarns are acceptable; poor - frequent breakage affects the spinning efficiency.

[0094] Table 1

[0095]

[0096]

[0097]

[0098] The spinning oil prepared in Example 2 was sent for biocompatibility testing as an extreme case to evaluate the biocompatibility effect of the oil formulation. It should be noted that biocompatibility means that the substance does not produce toxicity, harm or immune response when in contact with living tissue and has biocompatibility. The test is carried out according to ISO 10993 or GB / T16886 standards, and the evaluation items include but are not limited to physical and / or chemical information, cytotoxicity, sensitization, irritation or intradermal reaction, material-mediated pyrogenicity, acute systemic toxicity, subacute toxicity, subchronic toxicity, chronic toxicity, implantation reaction, blood compatibility, genotoxicity, carcinogenicity, reproductive / developmental toxicity, degradation, etc.

[0099] In the present invention, the specific evaluation items of the biocompatibility of the spinning oil include: cytotoxicity (test standard is ISO 10993-5), sensitization reaction (test standard is ISO 10993-10), stimulation (test standard is ISO 10993-10), hemolytic reaction (test standard is ISO 10993-4), material-mediated pyrogenicity (GB / T 16886.11), acute systemic toxicity (test standard is ISO 10993-11), subacute and subchronic toxicity (test standard is ISO 10993-11), chronic toxicity (test standard is ISO 10993-11), implantation reaction (test standard is ISO 10993-6), and genetic toxicity (test standard is ISO10993-3). The test results are shown in Table 2.

[0100] Table 2

[0101] Biocompatibility Example 2 Cytotoxicity √ Allergic reactions √ Stimulate √ Hemolytic reaction √ Materials-mediated pyrogenicity √ Acute systemic toxicity √ Subacute and subchronic toxicity √ Chronic toxicity √ Implantation reaction √ Genotoxicity √

[0102] It can be seen from Table 1 and Table 2 that the spinning oil provided by the present invention has both good fiber spinnability and biocompatibility, is highly safe as an implantable medical material, and is particularly suitable for preparing implantable medical fibers.

[0103] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0104] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A spinning oil, characterized in that: The spinning oil comprises 74.5 wt% to 93.9 wt% of purified water, 5 wt% to 20 wt% of polyethylene glycol, 1 wt% to 5 wt% of polyvinyl alcohol and 0.1 wt% to 0.5 wt% of polyvinyl pyrrolidone, and the conductivity of the spinning oil is 4.0×10 -4 S / cm~6.0×10 -4 S / cm.

2. The spinning oil according to claim 1, characterized in that The viscosity of the spinning oil is 20 mm 2 / s~50mm 2 / s.

3. The spinning oil according to claim 1, characterized in that The conductivity of the polyethylene glycol is 1.5×10 -4 S / cm~6.5×10 -4 S / cm.

4. The spinning oil according to claim 1 or 3, characterized in that The polyethylene glycol is selected from at least one of polyethylene glycol 200, polyethylene glycol 300, polyethylene glycol 400, polyethylene glycol 500 or polyethylene glycol 600.

5. The spinning oil according to claim 1, characterized in that The weight average molecular weight of the polyvinyl alcohol is 8000 to 50000; And / or, the alcoholysis degree of the polyvinyl alcohol is greater than or equal to 80%.

6. The spinning oil according to claim 1, characterized in that The weight average molecular weight of the polyvinyl pyrrolidone is 8000 to 50000; And / or, the K value of the polyvinyl pyrrolidone is 13-30.

7. The spinning oil according to claim 1, characterized in that The mass ratio of the polyethylene glycol to the polyvinyl alcohol is (1-5):

1.

8. Use of the spinning oil according to any one of claims 1 to 7 in the spinning of implant-grade medical fibers.

9. The use according to claim 8, characterized in that: The oiling rate of the spinning oil agent is 0.2% to 1.5%.

10. The use according to claim 8, characterized in that: The implant-grade medical fiber is one of medical UHMWPE fiber, medical PET fiber, medical PA fiber, medical PDS fiber, and medical PLGA fiber.